Konsep Komunikasi Data Antar Sistem Informasi Menggunakan Transmisi Kontrol Protokol (TCP) - Triyono, Joko; Harmastuti, Harmastuti; Tefa, Robertus (LPPM UNIKA Santo Thomas Medan, 2024)
Data communication between information systems is an important component in modern computer networks. The Input Process Output Cycle in an information system is something that will always happen and the output of an information system can become input for another information system, which is almost certain to happen. Current conditions cannot be denied that many information systems have been built and will always experience development. On the one hand, it is not easy to migrate to a new system, because in reality the old system is still stable. This research discusses the concept of data communication between information systems using Transmission Control Protocol (TCP). TCP is a protocol widely used in computer networks to ensure reliable data transmission between devices. From the research results, it was found that the TCP concept makes it possible to overcome data communication problems as expected.